Kepemimpinan Transformasional dalam Tata Kelola Pemerintahan dan Inovasi Sektor Publik: Kajian Literatur - Deby Alista; Putri Nurhayani; Cahaya Cahaya (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Transformational leadership is an important paradigm in strengthening modern governance that is oriented towards innovation, accountability, and public service. This research aims to examine the concepts, roles, and challenges of transformational leadership in the context of the Indonesian public sector through a literature study approach. The study was conducted on 15 open academic sources relevant to digital bureaucratic issues, apparatus work motivation, and organizational reform. The results of the study show that transformational leadership is able to increase performance effectiveness, strengthen employee commitment, and accelerate the digital transformation of the bureaucracy through an inspiring vision, intellectual stimulation, and individual attention to subordinates. In addition, this leadership contributes to the formation of a collaborative work culture and the improvement of public service innovations that are adaptive to the needs of the community. However, its implementation still faces structural obstacles, such as hierarchical culture, resistance to change, weak digital competence of the apparatus, and limited policy and human resource support. Therefore, a strong integration between transformational values, adaptive leadership competencies, and good governance principles is needed to drive sustainable and performance-oriented bureaucratic change that is superior to public performance.